Rhino-orbital cerebral mucormycosis in a child with type 1 diabetes: A case report - Mohamed Masmoudi; Mehdi Hasnaoui; Nouha Ben Abdeljalil; Rihab Guizani; Rihab Lahmar; Oussema Jaoued; Habiba Ben Sik Ali; Ahmed Rassas; Khalifa Mighri (SAGE Open Medical Case Reports, 2021)
Rhino-orbital cerebral mucormycosis is a rare but potentially severe fungal infection in children with high rate of morbidity and mortality. In pediatric patients, uncontrolled diabetes mellitus is considered to be a predisposing factor only in 15% of cases. To prevent and reduce mortality rate of this severe disease, early diagnosis based on clinical findings and biopsy is highly recommended. Herein, we report a case of rhino-orbital cerebral mucormycosis in a 12-year-old girl with type 1 diabetes to demonstrate that a multimodal management approach, involving early surgery which consists in frequent endoscopic sinus debridement and appropriate antifungal therapy, is essential to effectively reduce the spread of infection and achieve effective outcome.